Selective Decay of Intact HIV-1 Proviral DNA on Antiretroviral Therapy. (21st August 2020) - Gandhi, Rajesh T; Cyktor, Joshua C; Bosch, Ronald J; Mar, Hanna; Laird, Gregory M; Martin, Albine; Collier, Ann C; Riddler, Sharon A; Macatangay, Bernard J; Rinaldo, Charles R; Eron, Joseph J; Siliciano, Janet D; et al.
Abstract: Background: HIV-1 proviruses persist in people on antiretroviral therapy (ART) but most are defective and do not constitute a replication-competent reservoir. The decay of infected cells carrying intact compared with defective HIV-1 proviruses has not been well defined in people on ART. Methods: We separately quantified intact and defective proviruses, residual plasma viremia, and markers of inflammation and activation in people on long-term ART. Results: Among 40 participants tested longitudinally from a median of 7.1 years to 12 years after ART initiation, intact provirus levels declined significantly over time (median half-life, 7.1 years; 95% confidence interval [CI], 3.9–18), whereas defective provirus levels did not decrease. The median half-life of total HIV-1 DNA was 41.6 years (95% CI, 13.6–75). The proportion of all proviruses that were intact diminished over time on ART, from about 10% at the first on-ART time point to about 5% at the last. Intact provirus levels on ART correlated with total HIV-1 DNA and residual plasma viremia, but there was no evidence for associations between intact provirus levels and inflammation or immune activation. Conclusions: Cells containing intact, replication-competent proviruses are selectively lost during suppressive ART. Defining the mechanisms involved should inform strategies to accelerate HIV-1 reservoir depletion. Abstract : During long-term suppressive antiretroviral therapy, intact HIV-1 proviral levels selectively decline over time while defective HIV-1 proviral levels remain stable. As a result, the proportion of HIV-1 proviruses that are intact decreases over time on antiretroviral therapy.